Book reviews online - Philip Barker (Association for Learning Technology, 1997)
Many thousands of books are published each year, and even specialists find it difficult to keep abreast of new books in their disciplines, learning technology being no exception - indeed, in our subject-area the situation is beginning to reach saturation point. The bookreview procedure facilitates selection: a good review will capture the essential content of a book, and will comment on its quality, style, level of presentation, appropriateness, and perhaps value for money. Figure 1 shows the review process, its relationship to the production of books and learned journals, and the functional similarity between book reviews and abstracts of papers published in learned journals. Abstracts are often archived in online databases or on CD-ROM, in this way acting as an alerting and brief reference service. Book reviews can be treated in the same way. This paper discusses the use of servers (Internet or intranet) as a means of making them available to a global population. It also describes how such a facility could fit into a more general infrastructure for soliciting potential reviewers and drawing their attention to publications available for review.